Effects of long-term fire protection on Deciduous Dipterocarp Forest dynamics in Northeastern Thailand - NATTAKARNDA DUANGON; CHONGRAK WACHRINRAT; CHATCHAI NGERNSAENGSARUAY; SATHID THINKAMPHEANG; SUTHEERA HERMHUK; JAKKAPHONG THONGSAWI; WONGSATORN PHUMPHUANG; ANUSORN KULLAWONG; ARERUT YARNVUDHI; DOKRAK MAROD (Society for Indonesian Biodiversity, 2024)
Abstract. Duangon N, Wachrinrat C, Ngernsaengsaruay C, Thinkampheang S, Hermhuk S, Thongsawi J, Phumphuang W, Kullawong A, Yarnvudhi A, Marod D. 2024. Effects of long-term fire protection on Deciduous Dipterocarp Forest dynamics in Northeastern Thailand. Biodiversitas 25: 3141-3153. Forest fires are a significant problem that is often unmanaged, particularly their effect on tree regeneration. We aimed to clarify the forest dynamics and effects of climbers on tree regeneration after fire protection in a Deciduous Dipterocarp Forest in Northeastern Thailand. In 2004, permanent plots of 4 ha were established, and all trees with a Diameter at Breast Height (DBH) larger than 4.5 cm were labeled, measured, and identified. Monitoring was conducted in 2017 and 2022 when all trees with a DBH of more than 2 and 1 cm, respectively, were included and measured. The 92 species comprised 72 genera and 35 families with low species diversity. Tree density and basal area (DBH?1 cm) were 22.01 m2 ha-1 and 1,740 stem ha-1, respectively. The average recruitment rate was higher than the mortality rate throughout the study period (9.43 and 0.51 % y-1, respectively). However, it varied between periods. Long fire protection from 2004 to 2017 promoted the highest tree recruitment (12.67 % y-1, about 60 times to mortality rate) and regeneration of climbers on tree stems. It induced slightly higher mortality rates from 2017-2022, and approximately 18.87% of dead trees were damaged by dense climber cover. Our findings can help evaluate forest sustainability and support the planning of forest fire management strategies preserving species diversity in other tropical dry forests.